Microbiological screening for earlier detection of central venous catheter–related bloodstream infections. (15th July 2013) - Wagner, Jasmin; Schilcher, Gernot; Zollner‐Schwetz, Ines; Hoenigl, Martin; Valentin, Thomas; Ribitsch, Werner; Horina, Joerg; Rosenkranz, Alexander R.; Grisold, Andrea; Unteregger, Matthias; Troppan, Katharina; Valentin, Angelika; et al.
Abstract Background Catheter‐related bloodstream infections (CRBSIs) are currently detected with a reactive diagnostic policy, that is, application of tests to patients with clinically suspected CRBSI. The aim of our study was to evaluate whether CRBSIs could be anticipated in an earlier stage by microbiological screening using peptide nucleic acid fluorescence in situ hybridization (PNA FISH) with universal hybridization probes or acridine‐orange leucocyte cytospin (AOLC) tests in haemodialysis and haematological patients with CVCs in situ compared with routine test. Materials and methods Peptide nucleic acid fluorescence in situ hybridization (PNA FISH) and AOLC tests using blood samples from both CVC lines in patients undergoing haemodialysis were performed three times a week and from one CVC line in haematological patients were performed daily. Results were compared with those obtained from routinely performed CRBSI diagnostic tests. Results One hundred fifteen patients with 139 catheter periods were investigated. The mean observation time per catheter period was 25 days (IQR 13·5–43·5), resulting in 5615 CVC days with a total of 4839 tested blood samples. Five CRBSI cases were detected by routine measures resulting in a CRBSI rate of 0·9/1000 catheter days. Four of five CRBSIs could be anticipated by positive PNA FISH and AOLC tests 2–8 days before the diagnosis was established with routine measures. Conclusions The proactive anticipative strategy using microscopic examination of CVC blood samples to anticipate CRBSI in an earlier stage compared with routine measures is a new diagnostic approach in patients with CVCs and a high risk of developing CRBSI.